Critical Anthological Imagination: Looking Historically at Prisoners Writing About Themselves as Adult Learners in the United States (1966-2006) - Dominique T. Chlup (Adult Education Research Conference, 2007)
This paper presents some initial findings from an analysis of published anthologies written by prisoners in the U. S. about how they view their own educational advancement, schooling, and their role as adult learners within the context of their incarcerated lives.